Pendidikan Anak Shaleh Perspektif Al-Zarnuji Dalam Kitab Ta’lim Muta’allim - Ayyub, Ayyub; Mardiana, Dina (LPPM Institut Pendidikan Nusantara Global, 2024)
Children's education is carried out by cultivating good morals, protecting them from bad associations and is a way to get real life. This article discusses the education of pious children according to Al-Zarnuji in the book